Shallow Compaction Modeling and Upscaling: A One-Dimensional Analytical Solution and Upscaling - Zhang, Jingchen; Ma, Jingsheng; Couples, Gary D.; Osuji, Nicholas Izuchukwu (Frontiers in Earth Science, 2021)
Natural depositional processes frequently give rise to the heterogeneous multi-layer system, which is often overlooked but essential for simulation of a geological process. Sediment will undergo the large-strain process in shallow depth and small-strain process in deep depth. With the transform matrix and Laplace transformation, a new method of solving multilayer small-strain (Terzaghi) and large-strain (Gibson) consolidations is proposed. Corresponding results match the numerical results and other analytical solutions well. According to the method of transform matrix, which can consider the integral properties of multilayer consolidation, relevant upscaling method is developed. This method is more effective than the normally-used weighted average method, upscaling results indicate the upscaled properties of a multilayer system are varying in a consolidation process.